Effects of Early Childhood Climate on Cognitive Development and Home Environment - Wenjie Wu; Zhe Yang; Jun Hyung Kim; Ai Yue (Institute of Labor Economics (IZA), 2023)
Climate change poses a significant threat to the development of young children, but its impacts are not well known because of data and methodological limitations. Using a unique panel study in disadvantaged rural communities, we find that exposures to low temperatures undermine subsequent cognitive development before age 5, and reduce caregiver-child interactions and material investments. Results do not support income, health and temporary disruption in cognitive performance as potential channels. By undermining children's home environment, climate change may widen socioeconomic inequalities across households by their capacity to adapt, which is severely limited among disadvantaged households.
Keywords: I14; I18; J13; P25; 330; early childhood; cognitive skills; home environment; temperature; climate change; China